Extraction Of Ketapang And Mangrove Natural Dyes As Wisdom For The Development Of Ecological Batik In Pekalongan City - Klaski Putri, Krisanti; Tjahjono, Budi (International Journal of Science, Technology & Management, 2024)
This research explores the use of natural dyes extracted from ketapang leaves (Terminalia catappa) and mangrove wood (Rhizophora mucronata Poir) as environmentally friendly alternatives in the batik dyeing process in Pekalongan City. The experimental method was applied to pieces of cotton cloth dipped in natural dye extraction, with a variety of fixators in the form of alum, chalk and tunjung. The results showed that the type of fixator and pen frequency of dyeing influenced the intensity and character of the color on the fabric. The color produced from ketapang leaves with a tunjung fixator produces a blackish green nuance, while mangrove wood fixed with calcium hydroxide produces a brick red color. This research offers a sustainable solution for the batik industry through natural dyeing, supporting environmental preservation and public health in the Pekalongan batik center area.